The elasticity of substitution and labor-saving innovations in the Spanish regions - Cutanda, Antonio (Estudios de Economía, 2022)
This paper performs a nonlinear estimation of a normalized CES production function within a system of equations with a panel of Spanish regions for the period 1964-2013. It obtains an elasticity of substitution below one and identifies different rates of factor-augmenting technical progress. The results support for labor-saving innovations hypothesis for the Spanish case. Nevertheless, they do not support a relationship between the elasticity of substitution and the initial regional capital per worker. The results do not change if labor is adjusted by human capital.